Epizootic Newcastle Disease in Local Chickens Reared in South East Savannah Zone of Nigeria - Okwor, E.C.; Eze , D.C. (International Journal of Poultry Science, 2011)
A study on the outbreaks and prevalence of Newcastle Disease (ND) in village chickens in the savannah derived Eastern part of Nigeria was conducted based on cases submitted in two strategically located veterinary clinics. ND was diagnosed and confirmed by clinical signs, post mortem lesions and virus isolations in 11 day old embryonated chickens eggs. The study was carried out for a period of 3 years. Results showed similar distribution of outbreaks within the 3 year study period. Prevalence or outbreak of ND in village chickens was observed only during one period of the year, November-February period. This period coincides with the cold and harsh harmathan period usually seen from November to March in the Eastern part of Nigeria. The cold and harsh stress associated with this period is thought to worsen ND infected leading to spread and outbreaks. Veterinary awareness among the village farmers was also observed to be low in the control of ND in village chickens. Extension services involving education of the rural farmers, strategic vaccination prior to the period of outbreaks and biosecurity measures are recommended to help in the control of ND in village chickens.